Evaluating the effectiveness of mental health training on the knowledge and attitudes of non-specialist health workers in South Africa - Mahlakametsa, Mpho (Department of Psychiatry and Mental Health, 2025)
Mental disorders have a considerable impact on the rates of disability in the world. Economic data have consistently shown that the indirect losses resulting from poorly managed mental disorders continue to outstrip countries' health budgets. Given a significant shortage of health care professionals in low-and middle-income countries, particularly for mental health, and the unequal distribution of resources, a task-shifting approach has been proposed to broaden access to services using less specialised health care providers and reduce the treatment gap resulting from a shortage of human resources. The study observations have shown that this as a feasible option that may improve mental health outcomes. This study expanded on a pilot intervention study carried out by Sibeko and colleagues, which demonstrated that mental health training offered to non-specialised health workers' (NSHW) in the Western Cape province of South Africa had a positive impact on their knowledge, confidence, and attitudes. Method: This study analysed data collected as part of routine programmatic data collection of mental health training provided to 344 NSHW in various centres across South Africa. The mental health knowledge schedule and community attitudes towards mental illness tests were administered before and after the training was provided. The test scores were analysed using regression models to determine which of the demographic characteristics had an impact in the scores. Results: Seventy one percent of the training recipients were women, with 97% of them with a minimum education level of grade 8 or higher. The median age was 36, with the median duration of working as a NSHW of six years. There was an overall statistically significant increase in the knowledge score (pre-training median 43, post-training median 46, p-value < 0.01). nearly 90% recipients showed an openness to living next to individuals with mental illness. Following training, the recipients were less likely to report that people suffering from mental disorders were threatening. There only statistically significant change in attitude scores was in the social restrictiveness subscale (pre-training median 28, post-training median, 27 p-value <0.01). Conclusion: The training provided to the NSHW improved their knowledge and attitude scores, in keeping with the original study. We recommend continued training to upskill this cadre of health workers to enhance the screening, early recognition of, and intervention of mental disorders.